Ultrasound-Guided Injection of a Corticosteroid Technique for the Treatment of Degenerative Meniscal Tear - François Duprat, M.D.; Dany Mouarbes, M.D.; Emilie Berard, M.D.; Pierre Thomas, M.D.; Johan Laffort, M.D.; Etienne Cavaignac, M.D., Ph.D.; Marie Faruch Bilfeld, M.D., Ph.D. (Arthroscopy Techniques)
Degenerative meniscal tear is a chronic disorder that presents with knee pain, swelling, and loss of motion. It usually develops slowly on meniscal tissue that already has macroscopic and ultra-structural changes that affect its resistance to load. Conservative management, such as corticosteroid infiltration, is currently advocated as a first-line approach. However, it has been empirically observed that intra-articular injections do not appropriately alleviate pain because they do not target the trigger area of the meniscus and are quickly cleared from joints via synovial capillaries and lymphatic drainage. In recent years, there has been increased interest in the use of ultrasound guidance for meniscal and perimeniscal injection. Cadaveric specimens have offered optimal visualization of local anatomic structures, permitting safe and precise percutaneous delivery of medication in the meniscus. The vascularization is located mainly in the peripheral third of the meniscus, particularly on the perimeniscal capillary plexus. This is why this area has healing potential, in contrast to the free zone of the meniscus. The ultrasound-guided infiltration of the meniscal wall is a technique that is more targeted and more effective on the trigger zone.